Metagenomic Resolution of Functional Diversity in Copper Surface-Associated Marine Biofilms - Zhang, Yimeng; Ma, Yan; Zhang, Ruiyong; Zhang, Binbin; Zhai, Xiaofan; Li, Wangqiang; Xu, Liting; Jiang, Quantong; Duan, Jizhou; Hou, Baorong (Frontiers in Microbiology, 2019)
We used metagenomic sequencing combined with morphological and chemical analyses to investigate microbial taxa and functions related to copper-resistance and microbiologically influenced corrosion in mature copper-associated biofilms in coastal seawater for 44 months. Facultative anaerobic microbes such as Woeseia sp. were found to be the dominant groups on the copper surface. Genes related to stress response and possible heavy metal transport systems, especially RNA polymerase sigma factors (rpoE) and putative ATP-binding cassette (ABC) transport system permease protein (ABC.CD.P) were observed to be highly enriched in copper-associated biofilms, while genes encoding DNA-methyltransferase and RNA polymerase subunit were highly enriched in aluminum-associated biofilms and seawater planktonic cells, respectively. Moreover, copper-associated biofilms harbored abundant copper-resistance genes including cus, cop and pco, as well as abundant genes related to extracellular polymeric substances (EPS), indicating the presence of diverse copper-resistance patterns. The proportion of dsr in copper-associated biofilms, key genes related to sulfide production, was as low as that in aluminum biofilm and seawater, which ruled out the possibility of microbial sulfide-induced copper-corrosion under field conditions. These results may fill knowledge gaps about the in situ microbial functions of marine biofilms and their effects on toxic-metal corrosion.